2017
DOI: 10.1093/gerona/glx058
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR Quantitation of Muscle Mitochondrial DNA: Age, Fiber Type, and Mutation-Induced Changes

Abstract: Definitive quantitation of mitochondrial DNA (mtDNA) and mtDNA deletion mutation abundances would help clarify the role of mtDNA instability in aging. To more accurately quantify mtDNA, we applied the emerging technique of digital polymerase chain reaction to individual muscle fibers and muscle homogenates from aged rodents. Individual fiber mtDNA content correlated with fiber type and decreased with age. We adapted a digital polymerase chain reaction deletion assay that was accurate in mixing experiments to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Frozen muscle samples were powdered under liquid nitrogen using a mortar and pestle. Approximately 25mg of powdered muscle was used in DNA isolation as previously described (Herbst et al, 2017). Quality control of the DNA was performed with UV spectrometry and gel electrophoresis.…”
Section: Mtdna Copy Number and Mtdna Deletion Frequency By Digital Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen muscle samples were powdered under liquid nitrogen using a mortar and pestle. Approximately 25mg of powdered muscle was used in DNA isolation as previously described (Herbst et al, 2017). Quality control of the DNA was performed with UV spectrometry and gel electrophoresis.…”
Section: Mtdna Copy Number and Mtdna Deletion Frequency By Digital Pcrmentioning
confidence: 99%
“…Quality control of the DNA was performed with UV spectrometry and gel electrophoresis. A 5-prime nuclease cleavage assay and chip-based digital PCR (dPCR) was used to quantitate copy numbers for nuclear DNA (nDNA), total mtDNA, and mtDNA deletions with specific primer/probe sets for each as previously described (Herbst et al, 2017). Samples were diluted to the manufacturer's recommended target range (200 to 2,000 copies per microliter) in 17.5 microliter reactions using QuantStudio 3D Digital PCR Master Mix v2 (ThermoFisher; Waltham, MA) and loaded onto Quantstudio 3D digital PCR 20K Chip (Version 2, ThermoFisher; Waltham, MA).…”
Section: Mtdna Copy Number and Mtdna Deletion Frequency By Digital Pcrmentioning
confidence: 99%
“…Data on TEE in COPD are scarce and sometimes contradicting, which may be related to the use of different methodology or patient characteristics. Based on the available evidence, it seems that in particular the emphysematous phenotype is prone to increased TEE, as high values are more often observed in patients with low carbon monoxide diffusing capacity [117][118][119]. This is in line with a positive effect of lung volume-reduction surgery on body weight in emphysema, although surgical intervention might not only decrease energy requirements but also improve dietary intake by alleviating dyspnea [120].…”
Section: Increased Energy Expenditurementioning
confidence: 86%
“…Numerous studies have shown that REE is raised [121][122][123]. This is more prevalent in emphysema [124,125], during acute exacerbations [126], and appears inversely correlated with forced expiratory volume in 1 s when comparing different studies [118,119,122,127]. Highest values are found among weight-losing patients [122].…”
Section: Increased Energy Expenditurementioning
confidence: 99%
See 1 more Smart Citation